The Effects of the Addition of Banana Puree to the Total Number of Total Probiotic Bacteria, pH Value and Organoleptic Characteristics of the Synbiotic Yoghurt Made from Goat Milk and Banana Puree - Nafila Fidina; Een Sukarminah; Debby Moody Sumanti (Universitas Padjadjaran, 2018)
Synbiotic yoghurt is a yoghurt with the addition of prebiotics and lactic acid bacteria (LAB) that serves as probiotic which helps to improve digestion, able to survive in gastric acid condition and able to improve immune system. The milk that was used in this study is Saneen goat milk which has higher digestibility than cow milk. The banana used in this study will be processed into puree form. The purpose of study was to determine the concentration of banana puree on synbiotic yoghurt made from goat milk and banana puree with the best microbiological, pH value, viscosity and organoleptic characteristics. The research method used was randomized block design with 4 treatments and 3 replications. Synbiotic yoghurt was made with difference concentrations of banana puree of 25%, 50%, 75% and 100%. The 50% addition of banana puree produced the best synbiotic yoghurt with 4,15 pH, 9,43 Log cfu/ml and 9,16 Log cfu/ml total probiotic bacteria, and the organoleptic characteristics including color, flavor, taste, texture and overall appearance rather preferred by panelists.